Modulation of dopamine release in the nucleus accumbens by 5-HT1B agonists: involvement of the hippocampo-accumbens pathway. - Boulenguez, P; Rawlins, J; Chauveau, J; Joseph, M; Mitchell, SN; Gray, J (1996)
Changes in extracellular levels of dopamine (DA), DA metabolites DOPAC and HVA, and the serotonin metabolite 5-HIAA, were measured by microdialysis in the rat nucleus accumbens (n. acc) after treatments with serotonin (5-HT)1A (8-OH-DPAT) or 5-HT1B (RU 24969 and S-CM-GTNH2) receptor agonists. Subcutaneous injections of RU 24969 (0.02-2 mg/kg) dose-dependently decreased 5-HIAA levels (0 to -38%), and also induced long-lasting increases in DA levels (0 to +37%) and DOPAC (+11% at the dose 0.5 mg/kg) in the shell of the n. acc, whereas 8-OH-DPAT (0.25 and 0.5 mg/kg) reduced 5-HIAA levels (-25%) and very slightly increased DOPAC at the lower dose (+4%), but had no effect on DA levels. Three weeks after interruption of the subicular efferent projections, the increase in DA levels previously observed after systemic injections of RU 24969 was abolished. Microinjections of RU 24969 (10 micrograms/microliter) or S-CM-GTNH2 (3 micrograms/microliter) into the ventral subicular area reproduced the effects of systemic injections of RU 24969 cn DA levels and increased DOPAC (+13%; +19%, respectively) and HVA levels (+23%; +24%), with no significant change in 5-HIAA. It is concluded that: (1) serotonin interacts with the mesolimbic dopaminergic system through 5-HT1B, but not 5-HT1A, receptors: and (2) serotonin interaction with the mesolimbic dopaminergic system involves postjunctional 5-HT1B heteroreceptors located in the ventral subicular area, which modulate the activity of glutamatergic hippocampo-accumbens pathways and only secondarily alter DA levels in the n. acc. The possible relevance of these results for schizophrenia is discussed.